The Mother of the Lord. Volume 1: The Lady in the Temple. By Margaret Barker - Jarrell, Robin (The journal of theological studies, 2014)
Margaret Barker has perhaps singlehandedly created a subgenre of the Origins of Christianity known as ‘Temple Theology’. In her latest work (the first of two volumes), she takes on her most ambitious project to date: to find the traces of the feminine divine (the Lady) which were lost in early Israelite culture and myth but which were remembered by the earliest Christians. Barker's detailed arguments and analysis of her topic is nothing short of encyclopedic—she covers vast amounts of ground with insightful detail., Barker argues that the end of the first Temple began with a cultural revolution centred around Josiah's reforms which introduced ‘the law book’ (Deuteronomy) and that those reforms were cultural as well as theological.